150k views
1 vote
What are the first two steps to solve this equation 4(2x - 3) = 1

2 Answers

3 votes

Answer & Step-by-step explanation:

Step 1: Use the distributive property


4(2x)+4(-3)=1\\\\8x-12=1

Step 2: Use the inverse property. Add 12 to both sides.


8x-12+12=1+12\\\\8x=13

:Done

Step 3: Inverse operations. Divide both sides by 8.


(8x)/(8)=(13)/(8)\\\\x=(13)/(8)

User HPJAJ
by
5.4k points
4 votes

Answer:

x=13/8

Explanation:

8x-12=1

8x=13

x=13/8

User Mohamed Anser Ali
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.